PENDISAINAN HYPOTETICAL LEARNING TRAJECTORY (HLT) MENGGUNAKAN KONTEKS MUSEUM TIMAH PANGKALPINANG - Fitri Apriani; Putri Cahyani Agustine (Universitas Muhammadiyah Tangerang, 2019)
Difficulty in understanding the concept of angle because of learning of angle is only explain, give examples, and practice, so there are still many students who have difficulty understanding the concept of angle. Angle is one of the most basic concepts to understanding geometry and should have been understood and mastered since elementary school in terms of length and angle so as not to cause students difficulties in learning angles in high school. PMRI was chosen because it can lead students to understand mathematical concepts, which in this study is the concept of angles. The aims of this study is to design a hypothetical learning trajectory in angle by using context of the Museum Timah Pangkalpinang as a tool in understanding the concept of angles. This study was using design research approach, with three stages of research are preparing for the experiment, the experimental design, retrospective analysis. The Hypothetical Learning Trajectory (HLT) was developed from a series of corner material learning activities using context of the Museum Timah Pangkalpinang. HLT is generated with 4 activities, that are observe museum buildings and mining equipment,determine the types of angle, determine the angle using the steps outlined in LKPD, and completed the questions.Keywords: Angle, Museum Timah, PMRI, HLT